2021
DOI: 10.1123/wspaj.2020-0062
|View full text |Cite
|
Sign up to set email alerts
|

Are Coaches of Female Athletes Informed of Relative Energy Deficiency in Sport? A Scoping Review

Abstract: In the last decade, there has been greater appreciation of the harmful consequences of Relative Energy Deficiency in Sport (RED-S), particularly in adolescent female athletes. Coaches act as both important moderators in the development of the condition and as identifiers of athletes at risk. Research suggests that coaches lack knowledge on this topic. At present, it is unclear if RED-S education is incorporated into coach accreditation pathways. The aim of this scoping review was to describe the extent to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…In addition, due to increased knowledge of RED-S also among male athletes [2], future studies should also include male participants. Further, coaches from endurance sports who dictate the energy demands of training and are in a prime position to observe changes in athletes' health and performance, are not well enough educated about RED-S [77]. Cultural revolutions and changes in social norms are needed [25], and therefore, future studies should not only include individual athletes, but also their coaches, health professionals, entire teams, clubs, and sports organizations.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition, due to increased knowledge of RED-S also among male athletes [2], future studies should also include male participants. Further, coaches from endurance sports who dictate the energy demands of training and are in a prime position to observe changes in athletes' health and performance, are not well enough educated about RED-S [77]. Cultural revolutions and changes in social norms are needed [25], and therefore, future studies should not only include individual athletes, but also their coaches, health professionals, entire teams, clubs, and sports organizations.…”
Section: Future Directionsmentioning
confidence: 99%
“…Contributing factors may include the perceived low priority of RED-S amongst coaches and within organisations, as well as lack of coach education [33]. Many high school coaches in the US lack formal health education [28], and a review of five national sporting organisations in Australia found only one (rowing) had formal education on RED-S within their coach accreditation pathways [34]. Only 7 % of Summer Olympic International Sports Federations undertake health-related programmes, guidelines or research activity into RED-S [35].…”
Section: Knowledge and Perceptions Of Red-s In Adolescentsmentioning
confidence: 99%
“…These results corroborated those of Tenforde et al [ 13 ] and Gillbanks et al [ 10 ] who reported that over half of health care providers (doctor, nurse practitioners, physical therapist, athletic trainer) had not heard of RED-S. In specific reference to coaches, fewer studies exist, but the findings from those that have explored this group suggest that knowledge of RED-S is limited, and that coaches are more concerned with performance outcomes than the long-term health of athletes [ 6 , 14 , 15 ]. Whilst the limited knowledge and awareness might be justifiable in many instances given RED-S is relatively new and many perceived this topic to fall outside of their scope of practice, there is little doubt that greater knowledge and awareness could be integral to minimising the risk of RED-S and support the recovery process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%